Vibration modulation sidebands mechanisms of equally-spaced planetary gear train with a floating sun gear. (15th August 2019) - Li, Yongzhuo; Ding, Kang; He, Guolin; Yang, Xiaoqing
Highlights: Response signal models of planetary gear train with a floating sun gear are built. Frequency features of exciting force direction and transfer path are analyzed. Characteristics and mechanisms of modulation sidebands are deduced. The model effectiveness is verified by both experimental and field vibration data. Effective feature indicators are obtained for fault diagnosis of floating sun gear. Abstract: The sun gear of planetary gear train is generally designed to float in the radial direction to achieve the uniform load distribution among different planet gears, but brings periodic gear mesh errors to generate more complicated vibration signals. There lack effective feature indicators for fault diagnosis at present. On the basis of researches on signal transfer path functions and measuring-direction projection functions of the gear mesh force, a set of vibration signal models are built to represent the modulation sidebands induced by a single planet gear mesh. Taking phase differences among equally-spaced planet gears into consideration, vibration modulation sidebands generating from meshes of multiple planet gears are further studied. The mechanisms of sidebands are obtained, especially the influences of floating sun gear on some specific frequency components. Vibration signals of a single-stage planetary gear train and a wind turbine planetary gearbox show good frequency consistencies with the model-based signal. The comparison analyses effectively verify the correctness of the proposed model. An important feature indicator is obtained to distinguish whether the planetary gear train is assembled with a floating sun gear, or whether the planetary gear train without a floating sun gear exists some distributed defects.